The inevitable specificity of cities. - (:unkn) unknown (L. Müller, 2014)
Was ist eine Stadt? Wodurch definiert sich ihre Spezifität? Was macht ihre Qualitäten aus? Eine Vielzahl von Akteuren interagieren im urbanen Raum, wobei sie Transformationsprozesse auslösen, die oftmals disparate Ziele verfolgen. Deshalb verläuft die Entwicklung der heutigen Stadt nicht linear und der Prozess einer globalen Urbanisierung mündet keineswegs in einem homogenen urbanen Raum. Der Band untersucht unter der Verwendung der Kategorien "Territorium", "Macht" und "Differenz" verschiedene Städte und urbaner Gebiete wie die Kanarischen Inseln, Hong Kong und Nairobi. Diese Fallstudien zeigen Unterscheidungsmerkmale der physischen und sozialen Existenz dieser Orte. Mit Beiträgen von Roger Diener, Mathias Gunz, Manuel Herz, Jacques Herzog, Rolf Jenni, Marcel Meili, Shadi Rahbaran, Christian Schmid und Milica Topalovic.

What is a city? What determines its specificity? What shapes its quality? The evolution of the contemporary city does not follow a linear movement. It is shaped by transformation processes that are directed toward often distant and conflicting goals. Even though cities are inscribed into global processes and networks, they develop their own specific ways of dealing with these conditions. They tend to produce and reproduce their own specificity, their own patterns and character traits. Using the categories of territory, power, and difference also lending the book its structure the texts analyze different case studies of cities and urbanized territories, ranging from the Canary Islands to Hong Kong and Nairobi, unfolding the distinctiveness of their physical and social existences. With contributions by Roger Diener, Mathias Gunz, Manuel Herz, Jacques Herzog, Rolf Jenni, Marcel Meili, Shadi Rahbaran, Christian Schmid, and Milica Topalovic
Keywords: Stadt; Großstadt; Urbanität; Stadtentwicklung; Dichte; Bebauung; Stadtstruktur; Segregation; Strukturwandel; Macht; Differenz; Ungleichheit; Territorium; Informelle Siedlung; Gated Communities; Migration